فارسی کلام غالب کی شروح کا تعارف اور تنقیدی مطالعہ - Dr. Ali Kavousi Nejad (Khayaban - خیابان, 2022)
Mirza Asadullah Khan Ghalib took pride in his Persian poetry and considered it to be his most distinguished achievement. In his times, Ghalib’s command on Persian was well known in Indian subcontinent. Although Mughal empire was on brink of extinction, Ghalib’s Persian poetry at that time was enjoying its prime. Maulana Altaf Hussain Hali penned a comprehensive book on Ghalib’s personality and Urdu poetry and the foremost commentary on Ghalib’s Persian prose and poetry was surfaced. Maulana Hali was followed by many other scholars and authors who wrote commentaries on Ghalib’s Urdu & Persian poetry to make it understandable for the masses. Separate commentaries were written on each genre of Ghalib’s poetry. This paper will focus on the commentaries of Ghalib’s Persian poetry and its critical analysis will be presented to Urdu readers to let them know how these commentaries were produced with monumental efforts of their authors.